Main characteristics of the foreign investment development of Belarus - Samakhavets, Maryia; Hrechyshkina, Olena (Bulletin of Geography. Socio-economic Series, 2020)
The purpose of this paper is to investigate the key economic and geographical characteristics of the investment development of Belarus and how these characteristics could evolve in the future. The evaluation of the investment development of Belarus is based on comparative economic analysis, spatial analysis research methods and the cartographic method. Our results indicate a stable, predictable and enabling investment policy as the main determinant for attracting investment. This is confirmed by changes in the spatial distribution of foreign investment inflows in the real economy of Belarus by countries for 2010 and 2018. The characteristics of Belarusian investment development are identified because of the need to intensify innovative performance in the strategic dimensions of sustainable development. Particular attention is paid to the development of special economic zones with preferential regimes in the Republic of Belarus. This paper provides important new insights into the future prospects for Belarusian investment development on the basis of identified specifics.